Signals of Opportunity in Low Earth Orbit - David José de Magalhães Freitas Braga Leite (2018)
The goal of this dissertation is to perform a preliminary study concerning availability requirements for successful navigation in orbit. A number of signal types will then be studied in order to verify requirement satisfaction, also to assess the feasibility of using signals of opportunity such as DTTV and LTE existent at Low Earth Orbit altitudes. One of the many problems in the aerospace domain is assisted navigation. GPS receivers used in LEO satellites are very expensive and a big part of the total budget is used to buy these components. Some of the conditions that could constraint the result would be the rate of observations necessary and the availability of stations with sufficient power and multifrequency transmission.